Thiamine as a metabolic resuscitator in septic shock: a meta-analysis of randomized controlled trials with trial sequential analysis - Sangla, Frédéric; Verissimo, Thomas; Faivre, Anna; Glauser, Térence; Cheah, Saw Kian; Assouline, Benjamin; Sgardello, Sebastian; Legouis, David (Frontiers in Medicine, 2023)
Objective: Septic shock is one of the most common reasons for admission to the Intensive Care Unit (ICU) and is associated with high mortality. Fundamentally, its management rests on antibiotics, fluid therapy and vasopressor use while many adjunctive therapies have shown disappointing results. Thiamine has recently gained interest as a metabolic resuscitator, though recent trials have tempered this enthusiasm, more specifically when thiamine is associated with ascorbic acid. However, thiamine use alone has been poorly investigated. Design: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) in septic shock patients to assess the effects of thiamine without ascorbic acid as an adjunctive therapy. Setting: PubMed, Embase and the Cochrane library databases were searched from inception to April of 2023. Data were extracted independently by two authors. The main outcome was mortality. Subjects: We included RCTs comparing standard care using thiamine alone, to standard care or placebo, in patients admitted to the ICU with sepsis or septic shock. Main Results: We included 5 RCTs (n=293 patients). In this analysis, use of thiamine alone did not significantly change mortality, RR 0.87 (95%CI 0.65; 1.16, I2=21%) p= 0.34. Conclusions: Current RCTs did not show an improvement in mortality when using thiamine in septic shock patients as an adjunctive therapy. However, these trials are largely underpowered for a definitive conclusion to be drawn. Further studies are therefore needed .to assess the effects of thiamine without ascorbic acid as an adjunctive therapy.